Genome Assembly of Methicillin-Resistant Quality Control Strain Staphylococcus aureus CDC73-57501 (ATCC 29247) - Daligault, H. E. (American Society for Microbiology, 2014)
Staphylococcus aureus is a major cause of bacterial infections in the United States, with high percentages of serious infections resistant to a variety of β-lactam antibiotics. Here, we present the scaffolded genome assembly into 16 contigs of S. aureus CDC73-57501 (ATCC 29247), a methicillin-resistant quality control strain.